2021
DOI: 10.17159/2223-0386/2021/n25a2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Zambian Senior Secondary History Examination between the Old and Revised Curriculum using Blooms Taxonomy

Abstract: IThe 2013 Education reform in Zambia is one of the significant changes that brought about a shift in assessment. To understand the changes that have taken place in the 2013 revised curriculum, and to determine the claims by the Ministry of General Education that the revised curriculum is based on higher order thinking, this study evaluated the Examination Council of Zambia's Grade 12 History examination past papers. Qualitative content analysis was used as a research method and document study. A descriptive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…The third finding relates to the cognitive levels of the reviewed summative assessments, which showed that the assessments were mostly pitched at lower cognitive levels of blooms' taxonomy; 'remembering' and 'understanding' levels (Anderson & Krathwohl, 2001). Similar findings have been found in several studies (Kabombwe et al, 2021;Shukla & Dungsungnoen, 2016). This finding is concerning because it implies that the quality of assessments is compromised (Anees, 2017), in the sense that students could achieve high scores from summative assessments but lack higher order thinking skills, which are essential for solving problems and making rational decisions in society and in workplace (Junus, et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The third finding relates to the cognitive levels of the reviewed summative assessments, which showed that the assessments were mostly pitched at lower cognitive levels of blooms' taxonomy; 'remembering' and 'understanding' levels (Anderson & Krathwohl, 2001). Similar findings have been found in several studies (Kabombwe et al, 2021;Shukla & Dungsungnoen, 2016). This finding is concerning because it implies that the quality of assessments is compromised (Anees, 2017), in the sense that students could achieve high scores from summative assessments but lack higher order thinking skills, which are essential for solving problems and making rational decisions in society and in workplace (Junus, et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…The selection of these quality measures was guided by the LINQED Quality Assurance Framework for Student assessment (Educational network LINQED, 2011), which include fitness for Purpose (alignment with course objectives and content), authenticity and cognitive complexity. These assessment quality measures have been used in many studies (Gareis & Grant, 2015;Kabombwe, Machila, & Sikayomya, 2021). Measurement of assessment alignment with course objectives involves relating assessment items to the objectives specified for the course under review, while measurement of content validity involves matching assessment items with course content (Gareis & Grant, 2015).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The third finding relates to the cognitive levels of the reviewed summative assessments, which showed that the assessments were mostly pitched at lower cognitive levels of blooms' taxonomy; 'remembering' and 'understanding' levels . Similar findings have been found in several studies (Kabombwe et al, 2021;Shukla & Dungsungnoen, 2016). This finding is concerning because it implies that the quality of assessments is compromised (Anees, 2017), in the sense that students could achieve high scores from summative assessments but lack higher order thinking skills, which are essential for solving problems and making rational decisions in society and in workplace (Junus, et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Measurement of assessment alignment with course objectives involves relating assessment items to the objectives specified for the course under review, while measurement of content validity involves matching assessment items with course content (Gareis & Grant, 2015). The revised Bloom's taxonomy of educational objectives has been used extensively to determine the cognitive levels at which assessment items are pitched (Kabombwe, Machila, & Sikayomya, 2021;Anees, 2017). The measurement of assessment authenticity, which denotes an assessment's applicability to real-life situations has often involved the use of Wiggins' framework for authentic assessment (Wiggins, 1990).…”
Section: Conceptual Frameworkmentioning
confidence: 99%